Returning the favor: Positive employee responses to supervisor and peer support for training transfer - Tian, Amy; Cordery, J.; Gamble, J. (-, 2016)
Drawing on social exchange theory and associated notions of reciprocity, we argue that interpersonal support for training transfer in the workplace is associated with increased employee task performance and organizational citizenship behavior (OCB) and reduced turnover intention. We test our hypotheses using survey data from 786 Chinese retail employees. The findings show that when employees perceive high levels of supervisor/peer support for training transfer, they are more likely to deliver higher levels of task performance and OCB in response, which in turn, lead to reduced turnover intention. We also found that the strength of the relationship between supervisor/peer support for training transfer on individuals’ OCB varied across regions within China. The results confirm the moderating role of regional context (coastal and inland regions) on the relationship between supervisor/peer support for training transfer on individuals’ OCB, with a stronger effect found in less economically developed inland regions. The moderating effect of region indicates that cross-cultural researchers need to be aware of possible within-country variations in employee attitudes and values.